A questionnaire-based survey among clinicians and postgraduates regarding knowledge, awareness and practice of p-drug in Government General Hospital, Rangaraya Medical College, Kakinada - Kanthi, Grandhi Ramya; Prayaga, Usha Kiran (International Journal of Basic & Clinical Pharmacology, 2019)
Background: P-drug is a personal or preferred or priority choice drug of a clinician. The aim of the study is to evaluate knowledge, awareness, practice of p-drug which helps the clinician to prescribe drugs rationally. Methods: The study was a prospective cross-sectional pre-validated questionnaire-based study conducted in Government General Hospital, Rangaraya Medical College, Kakinada. During the study period a total of 300 members were enrolled and instructed to fill the questionnaire forms. These filled forms were collected and data were analyzed. Results: Out of 300 members, 240 filled the questionnaire, and these forms were evaluated. Among them 16.6% were aware of p-drug, 27.5% were aware of P treatment, 32.5% were not including FDC’s in their p drug list, 28.33% were aware of advantages of prescribing P drug and 82% felt that teaching programs were needed for preparing p drug list. Conclusions: For promoting and achieving rational use of medicine, P drug concept is one of the milestones. As few were aware of p-drug concept, institutional teaching review board should conduct teaching programs regarding p drug concept.